Adult retinopathy of prematurity: treatment implications, long term sequelae, and management. Issue 5 (September 2021) - Chang, Emmanuel; Rao, Prethy
Abstract : Purpose of review: Classically, ROP has been considered a neonatal disease only; however, pediatric ophthalmologists and retinal specialists worldwide are recently facing a new paradigm shift. retinopathy of prematurity (ROP) is now considered a lifelong disease that extends well into adulthood. The purpose of this review is to describe the adult ROP anatomy and discuss the late sequelae and management of this disease. Recent findings: Neonatal ROP treatments affect both anterior and posterior segment anatomy. Anterior segment changes secondary to inflammation and posterior ciliary nerve ablation range from acute to chronic pathology, including cataract, secondary glaucoma, and corneal decompensation. Persistent avascular retina can be present in previously treated Type 1 ROP eyes after anti-vascular endothelial growth factor or in 'normal' untreated eyes that did not previously meet Type 1 ROP criteria. Persistent avascular retina is associated with lattice-like changes, retinal tears, and detachments. The location and extent of the ridge, posterior hyaloidal contraction and adhesion, and persistent avascular retina all contribute to a spectrum of findings ranging from reactivation of neovascularization, tractional, rhegmatogenous, or exudative detachments. Summary: Understanding Adult ROP anatomy is critical in identification of retinal pathology and treatment choice. ROP patients require lifelong monitoring.